Synthesis of agricultural land system change in China over the past 40 years - Sun, Zhanli; You, Liangzhi; Müller, Daniel (Taylor and Francis, 2019)
Representing one of the core challenges of sustainable development is the persistent tension between increasing agricultural productivity to feed, clothe, house, and fuel the world’s growing population in the near term and ensuring environmental quality and resource sustainability to support humanity’s existence in the long term (Swinton, Lupi, Robertson, & Hamilton,2007; Zhang, Ricketts, Kremen, Carney, & Swinton,2007). These opposing pressures point to the need for greater evidence-based discourse on competing uses of land, spatial patterns of land use, and their impact on food availability and well-being. This is particularly so in China, which faces enormous pressure to increase food production and protect depleted natural resources and deteriorated environments.